Analysis of the Use of Graphic, Audiovisual and Computer Media in Indonesian Language Learning in Elementary Schools - Wulandari, Retno; Aminah, Siti; Pratiwi, Veronica Unun; Nugrahaini, Farida (UIR PRESS, 2024)
This research aims to describe the use of learning media in Indonesian language learning used by teachers and students at SDN Jati 2 Masaran. There is an urgency for learning media in elementary schools in the current digital era. First, using media can create a special attraction in learning. Interesting learning media can provide a pleasant learning experience for effective learning. Learning media can help students understand concepts more easily and quickly. Third, increase student participation. This can increase student involvement and participation in learning. Fourth, increase student creativity. This research method uses a qualitative descriptive research type. Research data comes from observations and interviews with data sources of students and teachers in elementary schools. Data collection techniques through observation, interviews and documentation. The results of the research show that at SDN Jati 2 Masaran teachers have used graphic media in the form of whiteboards, KBBI, puzzles, and charts and audiovisual media in the form of tape recorders, speakers and radio, as well as computer-based media in the form of powerpoint, web-based, and applications. in supporting Indonesian language learning.